e-Kiosk PPD Management Application - Abdul Malek, Nur Adlina Fareesya; Azhar, Nur Adlin Nadiah; Fakhrurrazi, Muhammad Afiq; Abdul Hamid, Mariam (Multidisciplinary Applied Research and Innovation, 2024)
Kiosk refers to a small booth that offers goods and services. Kiosks can be operated by humans or electronically. In this project, an eKiosk PPD Management application (eKiosk PPD) was developed for students to carry out business activities. The existence of this eKiosk application makes users no longer have to bother recording all business activities manually. Therefore, it can save time and also cost for users. The project uses a waterfall method which is suitable and simple for eKiosk applications to help refine the concept and create more useful applications. Flutter version 3.10.5 is used as a software that generates the codes to control overall programmes and build the interface for users to interact. eKiosk PPD was supported by Firebase as a database. eKiosk PPD able to calculate the profit, number of products that have been successfully sold and scheduling shifts.